Recent Advances in Perovskite‐Based Building‐Integrated Photovoltaics - Batmunkh, Munkhbayar; Zhong, Yu Lin; Zhao, Huijun (Advanced materials (Weinheim), 2020)
Perovskite‐based solar cells have attracted great attention due to their low cost and high photovoltaic (PV) performance. In addition to their success in the PV sector, there has been growing interest in employing perovskites in energy‐efficient smart windows and other building technologies owing to their large absorption coefficient and color tunability. The major challenge lies in integrating perovskite materials into windows and building facades and combining them with added functionalities while maintaining their remarkable power conversion efficiencies. Herein, advances that have been made in the application of perovskites to building‐integrated photovoltaics (BIPVs) in four areas are highlighted: semitransparent windows, colorful wall facades, electrochromic windows, and thermochromic windows. In addition, the opportunities and challenges of this cutting‐edge research area and important roadmaps for the future use of perovskites in BIPVs are discussed. The recent advances achieved in building‐integrated photovoltaics based on perovskite materials for four areas of applications, namely semitransparent windows, colorful wall facades, electrochromic windows, and thermochromic windows, are presented. Critical roadmaps on future developments of this cutting‐edge research field are provided.